2015
DOI: 10.1186/s13071-015-0954-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal associations of climatic drivers and malaria in the highlands of Ethiopia

Abstract: BackgroundThe impacts of interannual climate fluctuations on vector-borne diseases, especially malaria, have received considerable attention in the scientific literature. These effects can be significant in semi-arid and high-elevation areas such as the highlands of East Africa because cooler temperature and seasonally dry conditions limit malaria transmission. Many previous studies have examined short-term lagged effects of climate on malaria (weeks to months), but fewer have explored the possibility of longe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 39 publications
5
57
1
Order By: Relevance
“…Temperature was statistically significant and positively associated to count of malaria incidence in this study. The finding of this study is in line with previous studies of Jimma town(3), and Amhara region (38). Again it is supported by a study done in Yunnan Province, China which showed that annual average temperature was positively associated with the malaria incidence rate, according to the GWR model (39).…”
Section: Regression Analysissupporting
confidence: 92%
“…Temperature was statistically significant and positively associated to count of malaria incidence in this study. The finding of this study is in line with previous studies of Jimma town(3), and Amhara region (38). Again it is supported by a study done in Yunnan Province, China which showed that annual average temperature was positively associated with the malaria incidence rate, according to the GWR model (39).…”
Section: Regression Analysissupporting
confidence: 92%
“…In this study, five remote sensing based environmental variables-precipitation (TRMM_3B43_7), NDVI (MOD13C25), EVI (MOD13C25), nighttime land surface temperature (nLST) (MYD11C3), and daytime land surface temperature (dLST) (MYD11C3)-from TRMM and MODIS satellites were used to understand temporal patterns and the associations of remotely sensed variables with monthly dengue fever cases in Chitwan district of Nepal. These variables have been used for analysis in many previous studies [20,26].…”
Section: Remote Sensing Datamentioning
confidence: 99%
“…Malaria transmission in Ethiopia is seasonal and depends on favorable climatic and ecological factors for the growth of mosquito populations and the transmission of malaria parasites. In the Amhara Region, malaria cases typically peak at the end of the rainy season between September and December, and in some areas also have a smaller peak at the beginning of the rainy season in May and June [3,4]. Understanding how environmental factors trigger these seasonal outbreaks provides the basis for malaria early warning systems that can forecast changes in malaria transmission risk based on climate variability [5][6][7].…”
Section: Introductionmentioning
confidence: 99%